Cross-cultural adaptation and psychometric validation of the Flodén ATODAI instrument in the North American context - Anne Flodén; Maria Stadtler; Stephanie E. Jones Collazo; Tom Mone; Rick Ash; Bengt Fridlund (BMC, 2020)
Abstract Background Intensive and critical-care nurses are the key to successful donor management in the critical-care setting. No studies measuring attitudes toward organ donor advocacy existed before 2011, when the 51-item Swedish "Attitudes Toward Organ Donor Advocacy Scale" was developed. The aim of this study was to translate, adapt and establish the psychometric properties of the North American version of the Flodén ATODAI (Attitudes Toward Organ Donor Advocacy Instrument) in terms of validity and reliability. Methods A multi-step approach was used: Initial translation; Back-translation; Review and synthesis of these translations; Expert panel (N = 7) rated the prefinal version of the instrument for content validity index (CVI); International panel made adjustments guided by the expert panel. Reliability testing with test and retest of the adjusted 46-item version was conducted using intraclass correlation coefficient (ICC), weighted kappa (ҡ Weight ), sign test, and Cronbach's alpha coefficient (α), (N = 50); and finally Delphi technique procedure with a preselected Delphi panel (N = 15). Results The CVI was determined to be greater than the 0.05 significance level. Item level (I-CVI) ranged 0.82-1.0, with a mean of 0.97. Scale level (S-CVI) on the entire instrument was 0.97. Test-retest procedure was performed to estimate stability. In total, 34 of the items had good-to-high ICC. Accepting an ICC of ≥ 0.70 resulted in a total of 24 items. Homogeneity reliability was estimated by α and was calculated for these items where α = 0.90. In total, 20 of the items had a substantial or almost perfect ҡ Weight and 23 showed a moderate ҡ Weight . None of the items showed systematical differences. The Delphi technique procedure was used on the 22 items with ICC < 0.70 resulted in adjustments establishing that consensus was achieved. Conclusions Undertaking this multi-step, cross-cultural adaptation procedure has effectively ensured that the 46-item Flodén ATODAI [North American version] produces valid and reliable measurements.